Enhancements in full‐field PIXE imaging—Large area elemental mapping with increased lateral resolution devoid of optics artefacts. (20th May 2018) - Buchriegler, Josef; Klingner, Nico; Hanf, Daniel; Munnik, Frans; Nowak, Stanisław H.; Scharf, Oliver; Ziegenrücker, René; Renno, Axel D.; Borany, Johannes von
Abstract : The combination of a pn‐junction charge‐coupled device‐based pixel detector with a poly‐capillary X‐ray optics was installed and examined at the Helmholtz‐Zentrum Dresden‐Rossendorf. The set‐up is intended for particle‐induced X‐ray emission imaging to survey the trace elemental composition of flat/polished geological samples. In the standard configuration, a straight X‐ray optics (20 μ m capillary diameter) is used to guide the emitted photons from the sample towards the detector with nearly 70 000 pixels. Their dimensions of 48 × 48  μ m 2 are the main limitation of the lateral resolution. This limitation can be bypassed by applying a dedicated subpixel algorithm to recalculate the footprint of the photon's electron cloud in the detector. The lateral resolution is then mainly determined by the capillary's diameter. Nevertheless, images are still superimposed by the X‐ray optics pattern. The optics' capillaries are grouped in hexagonal bundles resulting in a reduced transmission of X‐rays in the boundary regions. This influence can be largely suppressed by combining a series of short measurements at slightly shifted positions using a precision stage and correcting the image data for this shifting. The use of a subpixel grid for the image reconstruction allows a further increase of the spatial resolution. This approach of image‐stacking and multiframe super‐resolution in combination with the subpixel correction algorithm is presented and illustrated with experimental data. Additionally, a flat‐field correction is shown to remove the remaining imaging inhomogeneity caused by non‐uniform X‐ray transmission. The described techniques can be used for all X‐ray spectrometry methods using an X‐ray camera to obtain high‐quality elemental images.